2012
DOI: 10.1096/fj.12-207472
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive β2‐agonists reverse neuromuscular involvement in murine Pompe disease

Abstract: Pompe disease has resisted enzyme replacement therapy with acid α-glucosidase (GAA), which has been attributed to inefficient cation-independent mannose-6-phosphate receptor (CI-MPR) mediated uptake. We evaluated β2-agonist drugs, which increased CI-MPR expression in GAA knockout (KO) mice. Clenbuterol along with a low-dose adeno-associated virus vector increased Rotarod latency by 75% at 4 wk, in comparison with vector alone (P<2×10(-5)). Glycogen content was lower in skeletal muscles, including soleus (P<0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 57 publications
7
41
2
Order By: Relevance
“…13 The current study demonstrated increased CI-MPR expression in quadriceps and gastrocnemius by a muscle-specific GAA expression vector, AAV2/8-MHCK7hGAApA (Fig. 3).…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…13 The current study demonstrated increased CI-MPR expression in quadriceps and gastrocnemius by a muscle-specific GAA expression vector, AAV2/8-MHCK7hGAApA (Fig. 3).…”
Section: Discussionsupporting
confidence: 56%
“…11,13 In this study, clenbuterol significantly increased the expression of CI-MPR in skeletal muscle (Fig. 3), including the quadriceps ( p < 0.01) and gastrocnemius ( p < 0.05).…”
Section: Ci-mpr Expression Is Increased By Gaa Expressionmentioning
confidence: 49%
See 3 more Smart Citations